Augmented reality in mobile commerce application - Lee, Guan Soon (2020)
In this project, an Android mobile commerce shopping application that is integrated with the Augmented Reality technology will be developed to resolve problems that is facing by current mobile commerce shopping application. The problems that is facing by current mobile commerce shopping application are the products that is selling in the mobile commerce application lack with a detailed visual representation that is view by the users. The integration of Augmented Reality technology in mobile commerce application is to increase the interaction and engagement of the users which will leading to a higher rate of purchasing the product.